Upaya Menumbuhkan Budaya Baca bagi Remaja di Desa Wonokarto Kecamatan Ngadirojo Kabupaten Pacitan Jawa Timur dengan Media Rumah Baca - Sutopo, Bakti; Firdiansyah, Febri (Indra Institute Research & Publication, 2024)
The efforts to improve the reading culture among adolescents in Wonokarto Village, Ngadirojo Sub-district, Pacitan District, East Java, is something that requires a gradual process or does not happen instantly. A reading culture needs to be instilled from an adolescent age when they are familiar with writing. Wonokarto Village is one of the villages located in Ngadirojo sub-district, Pacitan District, East Java, Indonesia, which has educational institutions ranging from primary to senior secondary. However, reading culture is not yet a priority for the community. The activity was conducted out of concern for the low interest in reading among teenagers around Wonokarto Village. Factors such as the difficulty of youth access to books, the lack of reading house facilities, and the dominance of game technology contribute to the low interest in reading in the neighbourhood. Therefore, the Wonokarto Village reading house has a big responsibility in promoting a culture of literacy in its community, especially among teenagers. The method used in this research is a qualitative method to describe the current situation. Data were collected through literature studies and direct interviews with research subjects, then analysed qualitatively. The results showed that teenagers in Wonokarto Village enthusiastically take part in activities at the reading house, by reading various types of books including fiction, nonfiction and comics. They were also active in interactions such as asking questions and listening to stories from researchers, which helped to encourage their interest in reading as well as their literacy development. It is hoped that the existence of the reading house can make a positive contribution in increasing adolescents' interest in reading in Wonokarto Village.